To'uluwa and the Magistrates: Coconuts and Yams, Governance and Indigenous Agency in the Trobriand Islands, Papua New Guinea, 1912–41. Issue 4 (2nd October 2018) - Connelly, Andrew
ABSTRACT: In the Trobriand Islands of today's Papua New Guinea, the coconut has long been mainly an accompaniment to yams – the primary staple food, central cultural icon and source of much of the chiefs' economic and political power. From the early 19th century, surplus yams were traded to Europeans operating in a regional economy, but the Assistant Resident Magistrates (ARMs) of the Australian government of colonial Papua in charge of the islands overlooked this industry in favour of copra, a global commodity. Beginning with a wholesale planting campaign in the 1910s and continuing with a 'native plantation scheme' in the 1920s, the ARMS exhorted Trobrianders to take time away from their beloved gardens to plant and tend coconut trees. Traces of resistance to this overzealous project come mainly through the voice and actions of Paramount Chief To'uluwa of Omarakana, as recorded by the ARMs in patrol reports and station journals. The colonial vision of a copra-based link to the global economy was dimmed by a fall in commodity prices in the mid 1920s, whilst the regional yam trade persisted for decades more. Hence the indigenous yam prevailed over the colonial coconut in a symbolic struggle for primacy in the islands, and the yam remains a symbol of a vibrant traditional Trobriand culture to this day.